Hope for success and life satisfaction among sport referees - Minda, Mateusz (Journal of Education, Health and Sport, 2020)
The article will present the results of research on the relationship between hope for success and life satisfaction in volleyball and football referees. The study involved 214 referees (104 from volleyball and 110 from football). In the presented study, the Hope for Success Questionnaire (KNS; Łaguna, Trzebiński, Zięba, 2005) and the Life Satisfaction Scale (SWLS; Juczyński, 2009) were used. The results of this study indicated that there are positive correlations between hope for success and life satisfaction in both group of volleyball and football referees. Additional analyzes also showed that there was a positive relationship between hope for success, willpower and life satisfaction in the group of female referees. Similarly, in the group of men, positive correlations were found between hope for success, the ability to find solutions, and willpower, and life satisfaction. The results of the research indicate the role of hope for success in the sense of life satisfaction. In the study group - sports referees, this topic seems to be particularly important and deserves further analysis.